Investigation of k-Îµ Turbulent Models and Their Effects on Offset Jet Flow Simulation - Boroomand, Mohammad Reza; Mohammadi, Amirhossein (Salehan Institute of Higher Education, 2019)
In the case in which relatively low thickness and high-velocity flow enter into the lower velocity fluid, the resulting interference field of these two flows is called the jet. This phenomenon is the dominant output of power plants and some of the dams. The jets can be divided into two categories of free jets and confined jets, caused by the distance from the discharge to limited boundaries points. The offset jet is a type of confined jet in which both free surface and wall boundaries are near the diffusion location. The jet flow due to the extreme curvature in the main flow path and the proximal portion of this flow with solid boundaries have characteristics that make it difficult to solve with simple turbulence models.In this research, the offset jet phenomenon and related issues have been investigated. For this purpose, the offset jet flow pattern and probable factors in the complexity of this model have been simulated using Fluent software which analyses fluid flow in a two dimensional and three dimensional finite volume method. The simulation of offset jet flow pattern has been performed with a focus on investigating different models of turbulence k-Îµ, also boundary conditions, various wall functions and other effective coefficients in the numerical model and the model results compared with test case data findings and validating results, the necessary approaches in numerical simulation of this phenomenon for using in the next stages had been taken.